Maṭbūʻāt al-Faqīh al-ʻAllāmah Saʻīd ibn Mubārak al-Ṣūrī - Ghaylānī, Ḥamūd ibn Ḥamad ibn Juwayd (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
Omanis gave their attention to writing and recording across the several sciences, and scarcely a period is free of scholarly and cultural contributions. Among those who enriched the Omani library is the learned jurist Saʿīd ibn Mubārak al-Ṣūrī al-ʿUmānī, whose manuscripts number some twenty, a number of which were printed; time and circumstance did not permit the printing of the remainder, owing to political and health conditions. This paper sheds light on the jurist's printed books: al-Durar al-Muḍīʾah fī Sharḥ al-Durūs al-Fiqhīyah; Qawl al-Khalaf wa-al-Aslāf fī Manʿ Bayʿ al-Awqāf; Durūs al-Tawḥīd; Durūs al-Tajwīd; Durūs al-Fiqh; and Qāʿidat al-Madrasah al-Ṣūrīyah al-Dīnīyah. The study adopts a descriptive-analytical method and consists of an introduction and a conclusion, the introduction being devoted to the shaykh and his scholarly course, while the first chapter treats his contributions.
MHF-PRINT2018-020
Keywords: Saʿīd ibn Mubārak al-Ṣūrī; Omani jurists; Printed works; Manuscript heritage; Bibliography; Islamic education